The Red Flag of Peace: Colonial Pacification, Cargo Cults and the End of War among the South Fore - Schwoerer, Tobias (Anthropologica, 2014)
Warfare among the South Fore ceased quickly after first contact in 1949. Three aspects of the process of colonial pacification profoundly changed incentive structures for local warfare: punishment by force of those groups continuing acts of aggression, incentives for giving up warfare and the emergence of hybrid forms of judicial institutions to peacefully settle conflicts. The Fore stress their own agency in ending warfare, mainly through participation in cargo cult movements with promises of valuables and "new things to come," which made it possible for all groups to end war at the same time.